Extracurricular Street Dancing for Adolescents’ Physical and Psycho-Social Health (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: Street dance is an engaging activity for young people, encouraging physical activity as part of their daily routine. Social skills such as communication, collaboration, and empathy are essential for both personal and professional life. These skills help individuals understand and regulate emotions, manage relationships, and resolve conflicts (Portela-Pino et al., 2021). A lack of mindfulness is becoming an increasingly relevant issue among youth, while adolescence is often marked by emotional challenges such as stress and anxiety. Research suggests that practicing mindfulness helps young people better cope with stress, enhances self-regulation skills (Makmee, 2022), and fosters empathy in relationships (Siffredi et al., 2021). This pilot, cross-sectional investigation explored: (1) the volume and intensity of physical activity, (2) key social-communication skills, and (3) mindfulness in youths who attend extracurricular street dance classes and examined how these variables interrelate.Methods: Sixty-three pupils aged 11–16 years were recruited to measure their socio-emotional skills (using Essential Social Skills Questionnaire, scale 1–5) and evaluate mindfulness (using the Mindful Attention Awareness Scale, MAAS-A, scale 1–4). In a sub-sample of 20 dancers, accelerometry (ActiGraph) captured activity during a standard 60-minute session.Results: Objective monitoring showed that, on average, participants spent 42.2 ± 11.0 minutes of each class in moderate-to-vigorous physical activity (MVPA) level. Girls displayed slightly higher overall social-skill scores (3.4 ± 0.3) than boys (3.1 ± 0.6) (p < 0.05). No sex-related differences emerged for either the total MAAS score (49.3 ± 10.6) or its item mean (3.5 ± 0.8). A modest negative correlation appeared between time spent in MVPA and the ‘emotional expression’ social-skill subscale (r = –0.45, p < 0.05), but this association disappeared after controlling for dance experience, sex, and age.Conclusion: Street dance classes provide adolescents with sustained bouts of health-enhancing physical activity and appear to nurture social interaction and mindful awareness. These findings lend support to the inclusion of street dance within after-school and youth-sport programmes aimed at fostering healthier, more self-aware young people.